2017
DOI: 10.1080/1031461x.2017.1279196
|View full text |Cite
|
Sign up to set email alerts
|

Asian Servants for the Imperial Telegraph: Imagining North Australia as an Indian Ocean Colony before 1914

Abstract: In the late nineteenth century, the officers of the Eastern Extension Australasia and China Telegraph Company provided north Australia with a cable connection to London via Java, Singapore, and India. The telegraph project prompted a new era of colonisation in tropical north Australia and the officers of the company sought to ensure that the north would be shaped according to their notions of Indian Ocean colonial culture. They insisted on employing Asian domestic servants in opposition to White Australian nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…In the second half of the 19th century, the resources, security and spatial organization of Indigenous peoples were radically disrupted by installation of the British telegraph system within today’s geographies of Indonesia and Australia (Martinez, 2017: 230–231; Owen, 2016: 298–299). Submarine telegraph cables were laid from Darwin to Banyuwangi in 1871 and from Banyuwangi to Broome in 1889 to link the relatively new telegraph networks in Australia and Southeast Asia.…”
Section: Eastern Telegraph Cables: Disrupting and Producing Communitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the second half of the 19th century, the resources, security and spatial organization of Indigenous peoples were radically disrupted by installation of the British telegraph system within today’s geographies of Indonesia and Australia (Martinez, 2017: 230–231; Owen, 2016: 298–299). Submarine telegraph cables were laid from Darwin to Banyuwangi in 1871 and from Banyuwangi to Broome in 1889 to link the relatively new telegraph networks in Australia and Southeast Asia.…”
Section: Eastern Telegraph Cables: Disrupting and Producing Communitiesmentioning
confidence: 99%
“…In 1937, a leading Japanese telecommunications engineer reported that the Dutch East Indies had become the centre of telecommunications in the East, producing equipment locally in case supplies from Europe were cut (Yang, 2010: 197). From a British colonial perspective too, Java was the ‘intermediary link, passing messages between Australia and London’ (Martinez, 2017: 230). The telegraph network supported an ‘Indian Ocean colonial culture’ (Martinez, 2017: 227) – and ‘the right to rule’ (Rizvi, 2017: 316) – that endured after Australia’s federation in 1901.…”
Section: Eastern Telegraph Cables: Disrupting and Producing Communitiesmentioning
confidence: 99%
See 3 more Smart Citations